The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1051/0004-6361/201935427
|View full text |Cite
|
Sign up to set email alerts
|

Proper motion in lensed radio jets at redshift 3: A possible dual super-massive black hole system in the early Universe

Abstract: In this paper, we exploit the gravitational lensing effect to detect proper motion in the highly magnified gravitationally lensed source MG B2016+112. We find positional shifts up to 6 mas in the lensed images by comparing two Very Long Baseline Interferometric (VLBI) radio observations at 1.7 GHz that are separated by 14.359 years, and provide an astrometric accuracy of the order of tens of µas. From lens modelling, we exclude a shift in the lensing galaxy as the cause of the positional change of the lensed i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 73 publications
2
45
0
Order By: Relevance
“…
We use a Chandra X-ray observation of the gravitationally lensed system MGB2016+112 at z=3.273 to elucidate presence of at least two X-ray sources. We find that these sources are consistent with the VLBI components measured by Spingola et al (2019), which are separated by ∼ 200 pc. Their intrinsic 0.5 -7 keV source frame luminosities are 2.6×10 43 and 4.2×10 44 erg s −1 .
…”
supporting
confidence: 86%
See 2 more Smart Citations
“…
We use a Chandra X-ray observation of the gravitationally lensed system MGB2016+112 at z=3.273 to elucidate presence of at least two X-ray sources. We find that these sources are consistent with the VLBI components measured by Spingola et al (2019), which are separated by ∼ 200 pc. Their intrinsic 0.5 -7 keV source frame luminosities are 2.6×10 43 and 4.2×10 44 erg s −1 .
…”
supporting
confidence: 86%
“…Such huge magnification is accompanied by spatial amplification that allows us not only to observe a source that would be otherwise too faint, but also to elucidate its structure as well as resolve spectra of individual lensed images of multiple sources. Radio observations reported by Spingola et al (2019) suggested possible dual-AGN-like structures with misaligned jets, and measured relative motions of components. If confirmed, MG B2016+112 would be the first gravitationally lensed dual AGN discovered to date.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, 0402+379 is a very nearby source, located at redshift z = 0.055, which corresponds to luminosity distance of only ∼ 220 Mpc. Gravitational lensing can provide the necessary spatial resolution to resolve SMBH binary systems like 0402+379 even at high redshift (see also Spingola et al 2019c). We show that it is possible to confine the radio emission of the lensed AGN down to 0.4 pc (0.05 mas) for CLASS B0712+472 and 0.08 pc (9 µas) for CLASS B1608+656.…”
Section: Tracing the Evolution Of Active Galaxies Using Large Samplesmentioning
confidence: 67%
“…We use Monte Carlo simulations to estimate the uncertainty of the reconstructed source position at radio and optical wavelengths following the same approach explained in Spingola et al (2019c). We briefly outline the approach below.…”
Section: Uncertainty On the Recovered Source Positionmentioning
confidence: 99%